Conserved molecular components for pollen tube reception and fungal invasion - Kessler, Sharon A.; Keinath, Nana (Science, 2010)
When pollen finds a compatible flower, it grows a pollen tube which must find the egg cell and release the sperm it carries. In searching for genes that affect pollen tubes in Arabidopsis , Kessler et al. (p. [968][1]; see the Perspective by [ Govers and Angenent ][2]) found a gene previously implicated in susceptibility to powdery mildew infection (the NTA gene). The NTA gene encodes a seven-pass transmembrane protein, which, in combination with a receptor-like kinase called Fer, is needed for successful pollen tube growth; both sets of proteins are also needed for successful powdery mildew invasion. These processes hence share common mechanisms of cell invasion, but where they diverge is in the outcome: embryogenesis or pathogenesis.